Integration of Knowledge and its Implementation in Yobe State University: Issues and Challenges - Ibrahim Dahiru Idriss; Adibah Abdul Rahim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract The study explores the concept of integration of knowledge and the foreseen issues and challenges in its implementation at Yobe State University, Yobe State, Nigeria. Integration of knowledge within the educational domain can be employed to foster a strong generation of interdisciplinary knowledge. This concept involves amalgamating two or more components, blending Western and Islamic knowledge. Muslims are encouraged to pursue various forms of knowledge. The study uses the qualitative approach to examine the role of integration of knowledge in addressing the designed objective which includes literature review from documented journal articles and books. The findings of the study show that integration of knowledge has the potential to address the issues and challenges confronting its implementation in Yobe State University, Nigeria. The paper asserts that the adoption of Western knowledge propagates secular influences within a nation’s educational framework, potentially eroding its Islamic identity. Consequently, harmonizing Islamic and Western knowledge should be viewed as a viable option for society to align their daily practices with authentic Islamic teachings. الملخص تستكشف الدراسة مفهوم تكامل المعرفة والقضايا والتحديات المتوقعة في تنفيذه في جامعة ولاية يوبي، ولاية يوبي، نيجيريا. يمكن استخدام دمج المعرفة في المجال التعليمي لتعزيز جيل قوي من المعرفة متعددة التخصصات. يتضمن هذا المفهوم دمج عنصرين أو أكثر، ومزج المعرفة الغربية والإسلامية. ويتم تشجيع المسلمين على متابعة أشكال مختلفة من المعرفة، مثل أصول الدين، والعقيدة، والشريعة، والأخلاق، والأخلاق. تستخدم الدراسة المنهج النوعي لفحص دور تكامل المعرفة في تحقيق الهدف المصمم والذي يتضمن مراجعة الأدبيات من مقالات المجلات والكتب الموثقة. تظهر نتائج الدراسة أن تكامل المعرفة لديه القدرة على معالجة القضايا والتحديات التي تواجه تنفيذه في جامعة ولاية يوبي، نيجيريا. وتؤكد الورقة أن تبني المعرفة الغربية ينشر التأثيرات العلمانية داخل الإطار التعليمي للأمة، مما قد يؤدي إلى تآكل هويتها الإسلامية. وبالتالي، ينبغي النظر إلى التوفيق بين المعرفة الإسلامية والغربية باعتباره خيارًا قابلاً للتطبيق للمجتمع لمواءمة ممارساته اليومية مع التعاليم الإسلامية الأصيلة